The Dialectics of Fiqh and Bugis-Makassar Customary Law in Shaping Local Islamic Norms - Muhammadong Muhammadong (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study examines the dialectical relationship between fiqh and Bugis Makassar customary law in the formation of local Islamic norms. The research is grounded in the reality that Islamic normativity in Bugis Makassar society is not shaped solely by formal religious texts, but also by living customary values that continue to guide social life. This interaction reflects a dynamic process in which Islamic teachings and local traditions negotiate, adapt, and reinforce one another in everyday practice. The study aims to analyze the patterns of this dialectic and to explain how both normative systems contribute to the construction of local Islamic norms. This research employs a qualitative approach with a library research design. Data were collected from classical and contemporary fiqh literature, studies on customary law, and scholarly works related to Bugis Makassar culture. The data were analyzed using descriptive analytical techniques through data reduction, thematic classification, and interpretive reading. The findings indicate that fiqh and customary law are not merely oppositional frameworks, but mutually constitutive sources of social legitimacy. Their interaction produces contextual Islamic norms that are religiously authoritative, culturally acceptable, and socially functional, thereby enriching the development of Islamic legal studies in plural societies within contemporary sociolegal discourse today.